Compact Oxford Italian dictionary Italian-English, English-Italian - Bulhosen, Pat.; Logi, Francesca; Riu, Loredana (Oxford Oxford University Press, 2013)
This dictionary covers over 90,000 words and phrases, and 120,000 translations of contemporary Italian and English. Includes all essential Italian and English words, based on findings from the Oxford Languages Tracker. More than just a dictionary, this handy reference book also includes extensive sections on grammar, culture, and communication, giving you the tools you need to communicate effectively and understand aspects of Italian culture. The grammar supplement provides full information on key points of Italian grammar, including verb tables for quick reference. The section on culture offers lively and useful information on life in both the Italian-speaking world and the English-speaking world, covering everything from political institutions to how weddings are celebrated. The communication supplement gives help with all types of correspondence, including example letters, emails, and résumés, and a guide to text me.
Text in English and Italian.
Keywords: Italian language -- English. -- Dictionaries; English language -- Italian. -- Dictionaries